Epidemiology, Pathophysiology, and Genetics of Primary Hyperparathyroidism. (17th October 2022) - Minisola, Salvatore; Arnold, Andrew; Belaya, Zhanna; Brandi, Maria Luisa; Clarke, Bart L.; Hannan, Fadil M.; Hofbauer, Lorenz C.; Insogna, Karl L.; Lacroix, André; Liberman, Uri; Palermo, Andrea; Pepe, Jessica; et al.
ABSTRACT: In this narrative review, we present data gathered over four decades (1980–2020) on the epidemiology, pathophysiology and genetics of primary hyperparathyroidism (PHPT). PHPT is typically a disease of postmenopausal women, but its prevalence and incidence vary globally and depend on a number of factors, the most important being the availability to measure serum calcium and parathyroid hormone levels for screening. In the Western world, the change in presentation to asymptomatic PHPT is likely to occur, over time also, in Eastern regions. The selection of the population to be screened will, of course, affect the epidemiological data (ie, general practice as opposed to tertiary center). Parathyroid hormone has a pivotal role in regulating calcium homeostasis; small changes in extracellular Ca++ concentrations are detected by parathyroid cells, which express calcium‐sensing receptors (CaSRs). Clonally dysregulated overgrowth of one or more parathyroid glands together with reduced expression of CaSRs is the most important pathophysiologic basis of PHPT. The spectrum of skeletal disease reflects different degrees of dysregulated bone remodeling. Intestinal calcium hyperabsorption together with increased bone resorption lead to increased filtered load of calcium that, in addition to other metabolic factors, predispose to the appearance of calcium‐containing kidney stones. A genetic basis of PHPT can be identified in about 10% of all cases. These may occur as a part of multiple endocrine neoplasia syndromes (MEN1–MEN4), or the hyperparathyroidism jaw‐tumor syndrome, or it may be caused by nonsyndromic isolated endocrinopathy, such as familial isolated PHPT and neonatal severe hyperparathyroidism. DNA testing may have value in: confirming the clinical diagnosis in a proband; eg, by distinguishing PHPT from familial hypocalciuric hypercalcemia (FHH). Mutation‐specific carrier testing can be performed on a proband's relatives and identify where the proband is a mutation carrier, ruling out phenocopies that may confound the diagnosis; and potentially prevention via prenatal/preimplantation diagnosis. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR). Abstract : The prevalence and incidence of PHPT vary around the world and depend on a number of factors, the most important being availability of serum calcium (and parathyroid hormone) measurement for screening, which in the Western world has shifted its presentation to an asymptomatic disorder. Clonally dysregulated overgrowth of one or more parathyroid glands together with reduced expression of CaSRs is the most important pathophysiologic basis of PHPT, which may also occur as a part of inherited syndromes or as a nonsyndromic isolated endocrinopathy in 10% of cases. Genetic testing has roles in establishing the clinical diagnosis, although its value requires assessments using GRADE (176) methodology, which is recommended for future consideration.